Association of Microalbuminuria with Glycemic Control amongType-2 Diabetes Patients: A Cross-Sectional Study (IAHS Medical Journal, 2026)
Background: Type 2 diabetes mellitus has been on the peak and a major cause of death due it’s complications in recent years. Diabetic patients with microalbuminuria are at increased risk of microvascular and macrovascular complications. Also, microalbuminuria is considered as a leading indicator of diabetic nephropathy. Poor glycemic control accelerates kidney damage, increasing the risk of end-stage renal disease. Identifying the relationship between glycemic control and microalbuminuria is crucial for early intervention and prevention of renal complications. The study aimed to investigate the association of microalbuminuria with glycemic control among type-2 diabetes patients in a regional tertiary hospital in Chattogram, Bangladesh.Materials and methods: This cross-sectional study was conducted in Department of Medicine, Endocrinology and Biochemistry in Chittagong Medical College, Chattogram from July 2022 to June 2023 among 119 people. The data were collected with face-to-face interview and HbA1c, UACR, BMI and WC were measured. The data were compiled and tabulated according to key variables and analyzed with IBM SPSS 29.0.2.Results: The mean age of the patients was 57.2 ± 9.7 years and there was a male predominance (67.2%) in the study. 50.4% had generalized obesity and 69.7% had central obesity. 83.2% had poor glycemic status and 41.2% patients had microalbuminuria. The proportion of microalbuminuria was higher in T2DM patients with uncontrolled glycemic status. Duration of diabetes and glycemic status were significantly associated with microalbuminuria.Conclusion: The study revealed that, frequency of microalbuminuria among type 2 diabetes is increasing in this contemporary era. Poor glycemic control is significantly associated with microalbuminuria in T2DM patients, emphasizing the need for screening of glucose markers and stringent glycemic management to prevent diabetic complications.IAHS Medical Journal Vol 8(2), December 2025; 43-48